Cytokines and Posthemorrhagic Ventricular Dilation in Premature Infants - Ambalavanan, Namasivayam; Carlo, Waldemar A.; McDonald, Scott A.; Das, Abhik; Schendel, Diana E.; Thorsen, Poul; Hougaard, David M.; Skogstrand, Kristin; Higgins, Rosemary D.; null (American Journal of Perinatology, 2012)
Objective To determine in extremely low-birth-weight infants if elevated blood interferon-γ (IFN-γ), interleukin (IL)-1β, IL-18, tumor necrosis factor-α (TNF-α), and transforming growth factor-β are associated with need for shunt following severe intraventricular hemorrhage (IVH) or with ventricular dilation following milder grades/no IVH.Study Design Whole blood cytokines were measured on postnatal days 1, 3, 7, 14, and 21. Maximum IVH grade in the first 28 days, and shunt surgery or ventricular dilation on subsequent ultrasound (28 days' to 36 weeks' postmenstrual age) were determined.Results Of 902 infants in the National Institute of Child Health and Human Development Neonatal Research Network Cytokine study who survived to 36 weeks or discharge, 3.1% had shunts. Of the 12% of infants with severe (grade III to IV) IVH, 26% had a shunt associated with elevated TNF-α. None of the infants without IVH (69%) or with grade I (12%) or II (7%) IVH received shunts, but 8.4% developed ventricular dilation, associated with lower IFN-γ and higher IL-18.Conclusion Statistically significant but clinically nondiscriminatory alterations in blood cytokines were noted in infants with severe IVH who received shunts and in those without severe IVH who developed ventricular dilation. Blood cytokines are likely associated with brain injury but may not be clinically useful as biomarkers for white matter damage.
Keywords: infant; premature; cytokines; hydrocephalus; intraventricular hemorrhage; intracranial hemorrhage